Occurrence and distribution of series long-chain alkyl naphthalenes in Late Cretaceous sedimentary rocks of the Songliao Basin, China - Lu, H.; Wang, L.; Song, Z.; Greenwood, Paul; Yin, Q. (Business Centre for Academics Societies Japan (Nihon Gakkai Jimu Senta), 2011)
A pair of series straight long-chain 2- and 1-alkyl naphthalenes (aNs) with alkyl chain carbon number up to 30 was detected in late Cretaceous sedimentary source rocks of the onshore Songliao Basin, NE China. Their sedimentary profile was shown to correlate positively with the relative abundances of several higher plant biomarkers including iP-iHMN and phenanthrene and weakly inversely with the relative abundance of alkylbenzenes. In contrast, the aNs distribution shows no relationship with hydrocarbon maturity indicators. The TOC, d13C profile and other molecular features (e.g., CPI, OEP, Pr/Ph, Ga/C31H) were consistent with transgressive/regressive water cycles of the palaeo-lake of Songliao Basin. Decreasing Pr/Ph values in the upper horizon indicative of increasingly anoxic conditions. The distinctive occurrence and distribution of the long-chain aN compounds on the profile of the SK-1 borehole may imply some unique source inputs under particular lacustrine environmental conditions. Copyright © 2011 by The Geochemical Society of Japan.